THE INVESTIGATION ON TWO STAY TWO STRAY TEACHING METHOD TOWARD STUDENTS’ READING COMPREHENSION - Sugianto, Sugianto; Tawali, Tawali (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The research was aimed at conducting the investigation on the effectiveness of Two Stay Two Stray Teaching Method Toward Students’ Reading Comprehension. The research address the research question on whether or not the two stay two stray teaching method effective in developing students’ reading comprehension. The type of the research was experimental study which consist of one class experiment with two pre test and post test. The subjects of the research were those students who were at the second years of SMPN 2 Jerowaru. The research instrument used multiple-choice test which measured the students’ reading comprehension. The result of data in this research were analyzed by means of descriptive and statistical analysis to determine the effectiveness of two stay two stray teaching method on students’ reading comprehension. The final hypothesis were made after finding out the statistical analysis result of the study.